MR. GEORGE HARVEY’S SHADOW ARCHETYPE AS SEEN IN ALICE SEBOLD’S THE LOVELY BONES - Dianika, Rafida Arge (Faculty of Letters, Dr. Soetomo University, 2018)
The thesis writer focuses on the analysis of Mr. George Harvey’s Shadow Archetype as seen in Alice Sebold’s The Lovely Bones. The objectives of the study are, to find out the types of Mr. George Harvey’s Shadow Archetype, the causes of Mr. George Harvey’s Shadow Archetype and the effects of Mr. George Harvey’s Shadow Archetype as seen in Alice Sebold’s The Lovely Bones on himself and on neighborhood (Joe Ellis). The thesis writer applies the theory of the psyche, archetypes and shadow archetype, the causes of shadow archetype, the effects of shadow archetype and she also applies a qualitative research.Keywords: The Psyche, Archetype, Shadow